Electrodes: A New Graphdiyne Nanosheet/Pt Nanoparticle‐Based Counter Electrode Material with Enhanced Catalytic Activity for Dye‐Sensitized Solar Cells (Adv. Energy Mater. 12/2015). Issue 12 (June 2015) - Ren, Hao; Shao, Hui; Zhang, Lijuan; Guo, Dong; Jin, Quan; Yu, Ranbo; Wang, Lei; Li, Yuliang; Wang, Yun; Zhao, Huijun; Wang, Dan
<x xml:space="preserve">Abstract</x> A graphdiyne nanosheet/Pt nanoparticle composite shows outstanding catalytic activity for the reaction of I3‐/I‐ redox pairs as the counter electrode for dye‐sensitized solar cells (DSSCs). In article number 1500296, Ranbo Yu and co‐workers report that it is easier to form a chemical interaction between Pt and graphdiyne, leading to enhanced electron transfer ability. The graphdiyne‐based DSSC shows comparable efficiency to precious Pt foil and higher efficiency than reduced graphene oxide/Pt nanoparticle composite, Pt nanoparticle‐based DSSCs.